2018
DOI: 10.1021/acsami.7b17771
|View full text |Cite
|
Sign up to set email alerts
|

Secondary-Phase Stochastics in Lithium-Ion Battery Electrodes

Abstract: Lithium-ion battery electrodes exhibit complex interplay among multiple electrochemically coupled transport processes, which rely on the underlying functionality and relative arrangement of different constituent phases. The electrochemically inactive solid phases (e.g., conductive additive and binder, referred to as the secondary phase), while beneficial for improved electronic conductivity and mechanical integrity, may partially block the electrochemically active sites and introduce additional transport resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
268
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 141 publications
(272 citation statements)
references
References 57 publications
(76 reference statements)
3
268
1
Order By: Relevance
“…This simplification has been well-established in the LIB literature. [1][2][3][4][5][6] With disparate CBD and active material particle sizes and morphologies, the resulting electrode contains a complex network of pores ranging from nanometer to micrometer length scales. Electrode battery macro-homogeneous electrochemical models often use porous electrode theory and thus abstract microstructural heterogeneity of composite electrodes using effective macroscopic properties.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This simplification has been well-established in the LIB literature. [1][2][3][4][5][6] With disparate CBD and active material particle sizes and morphologies, the resulting electrode contains a complex network of pores ranging from nanometer to micrometer length scales. Electrode battery macro-homogeneous electrochemical models often use porous electrode theory and thus abstract microstructural heterogeneity of composite electrodes using effective macroscopic properties.…”
mentioning
confidence: 99%
“…However, given the algorithmic nature of these approaches, a generated CBD phase is not necessarily realistic. To circumvent these imaging limitations, this work uses a physics-based CBD phase description recently proposed by Mistry et al, 6 which accounts for necessary evaporation dynamics that govern the interfacial arrangement of the CBD phase to generate a plausible CBD geometry within the pore domain. The method reasonably predicts effective properties as well as performance trends.…”
mentioning
confidence: 99%
“…Mesoscale modeling is commonly used to predict the effective electrical conductivity of the electrode for macroscale modeling [63], treating the effective conductivity as a static parameter. Recent works [19,21,22] have recognized that the CBD conductivity changes as a function of lithiation due to the mechanical forces generated from lithiation.…”
Section: Macroscale Propertiesmentioning
confidence: 99%
“…One important factor missing from much of the current mesoscale simulation literature is an accurate representation of the PVDF and carbon black composite binder domain (CBD) phase [53,63]. Experiments have shown that CBD has a significant impact on electrode performance [64][65][66][67][68].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation